PENGARUH BRAND IMAGE DAN JASA CASH ON DELIVERY (COD) TERHADAP KEPUTUSAN PEMBELIAN PADA MAY CAKES GG. SUBUR, BERINGIN. PEMATANG SIANTAR - Latifah Hanum Hutasuhut; Muhammad Radiansyah (CV. Barokah Publsiher, 2022)
This study analyzes the effect of brand image and cash on delivery on purchasing decisions at may Cakes Gg. Fertile, Banyan. Siantar District. The research method used in this research is descriptive quantitative. This research was conducted at the may cakes store Gg. Fertile, Banyan. Siantar District. The time of this research started in July 2022 until August 2022. The population in this study were consumers of may cakes Gg. Fertile, Banyan. Pematang Siantar which totaled 500 people. The results of using the slovin formula in this study the researchers took a sample of 83 consumers of May Cakes Gg. Subur, Banyan Siantar who use cash on delivery services. The analytical method used is multiple linear regression method using the SPSS 20 program. The results of this study indicate that the t-count > t-table (4.697 > 1.29236) and a significant value of 0.000 is less than 0.1 meaning that brand image has a significant effect on purchasing decisions of May Cakes Gg. Fertile, Banyan. Pematang Siantar, then Ha1 is accepted. The t-count > t-table (2.081 > 1.29236) and a significant value of 0.041 is less than 0.1, meaning that cash on delivery has a significant effect on purchasing decisions of May Cakes Gg. Fertile, Banyan. Pematang Siantar, then Ha2 is accepted. Fcount value (30.191) > Ftable (3.111), and a significance value of 0.000 <0.1, it can be concluded that Ha3 is accepted, meaning that the brand image variable (X1) and cash on delivery (X2) have a simultaneous effect on purchasing decisions ( Y). the adjusted coefficient of determination (R Square) is 0.656, this means that 65.6% of the dependent variable can be explained by the independent variable while the rest (100% - 65.6% = 34.4%) is explained by other variables outside the variables studied .